ANALISIS YURIDIS TERHADAP KEDUDUKAN AKTA WASIAT YANG TIDAK DIKETAHUI OLEH AHLI WARIS DAN PENERIMA WASIAT - ARLIANTI IMARIA SIMANJUNTAK (PREMISE LAW JURNAL, 2016)
A will is a statement made by someone on what they wish after they die. Frequently, a will maker does not inform his heir(s) to the will receiver. The condition when the heir(s) receiver does not know about it creates uncertainty on who should be responsible for the absence of information about the will. The problems of this research were what role a will, which was not known by the heirs or the will receiver, had for the natives; what legal consequences in the future a will was found. The will which was not known by the heirs and will receiver remained voidable and provable as long as it had been made in accordance with the formality of making will; however, the absence of information about the existence of this will made it unable to be implemented by the heirs and the will receiver who were natives. Keywords: Will, Notary, List of Will, To Whom It May Concern for Heirs